2004
DOI: 10.1097/01.brs.0000129028.25671.96
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Zealand White Rabbit Model of Spinal Pseudarthrosis Repair and Evaluation of the Potential Role of OP-1 to Overcome Pseudarthrosis

Abstract: This study establishes a model for treatment of pseudarthroses. OP-1, which has previously been shown to have 100% fusion rate in animal models, outperformed autograft and induced fusion in 82% of rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…The variety of defects currently investigated include segmental (Chen et al, 2002;Forriol et al, 2009;Reichert et al, 2012), drill Zhang et al, 2004), fusion (Blattert et al, 2002;Grauer et al, 2004;Magin and Delling, 2001) and ectopic implantation intramuscularly (Haidar et al, 2010a;Spiro et al, 2010) and subcutaneously (Sampath et al, 1992;Wei et al, 2007), which together emphasise the lack of and need for standardisation. Indeed, Takigami et al (2007) showed that anatomic location of the defect affected the efficacy of implanted BMP-7 on bone regeneration, where treatment of 10 mm femoral defects at the proximal and distal ends demonstrated 1.5-fold increased and 1.4-fold decreased bone formation.…”
Section: Gothard Et Al Tissue Engineered Bone and Clinical Translamentioning
confidence: 99%
“…The variety of defects currently investigated include segmental (Chen et al, 2002;Forriol et al, 2009;Reichert et al, 2012), drill Zhang et al, 2004), fusion (Blattert et al, 2002;Grauer et al, 2004;Magin and Delling, 2001) and ectopic implantation intramuscularly (Haidar et al, 2010a;Spiro et al, 2010) and subcutaneously (Sampath et al, 1992;Wei et al, 2007), which together emphasise the lack of and need for standardisation. Indeed, Takigami et al (2007) showed that anatomic location of the defect affected the efficacy of implanted BMP-7 on bone regeneration, where treatment of 10 mm femoral defects at the proximal and distal ends demonstrated 1.5-fold increased and 1.4-fold decreased bone formation.…”
Section: Gothard Et Al Tissue Engineered Bone and Clinical Translamentioning
confidence: 99%
“…Sternal separation in more than one location along the sternum also resulted in greater pain [32]. Many patients undergoing a median sternotomy are at risk for sternal nonunion, which can be affected by the degree of stability of fixation, reduction of blood supply (eg, as seen after internal mammary artery harvest), and comorbities such as diabetes and smoking [33][34][35]. The use of immunosuppressive drugs (eg, steroids) and the presence of osteoporosis also affect bone healing.…”
Section: Commentmentioning
confidence: 99%
“…The surgical procedure and fusion assessment techniques for rabbits entered into the pseudarthrosis study evaluating no graft, autograft, and osteogenic protein-1 have been reported, as cited in the Introduction above. 25 Single-level posterolateral L5-L6 intertransverse process autograft fusions were performed. Nicotine pumps were implanted subcutaneously to achieve serum levels of 10 -70 ng/ mL 21,25 levels, which are comparable to those of humans who smoke 20 -30 cigarettes per day.…”
Section: Specimen Preparation Our Institution's Animal Care Andmentioning
confidence: 99%
“…25 Relative fusion mass gene expressions were analyzed with reverse transcriptase polymerase chain reaction (RT-PCR). Angiogenic and osteogenic gene expressions were examined, including angiogenin, angiopoietin, intercellular adhesion molecule (ICAM), platelet-derived growth factor (PDGF)-␤, VEGF, BMP-2, BMP-7, type I collagen, and osteonectin, to characterize the effects of osteogenic protein-1 and autograft on pseudarthrosis repair.…”
mentioning
confidence: 99%